Motivation in the English Teaching- Learning Process (Original) (REDEL. Revista Granmense de Desarrollo Local, 2019)
In the System of Education the teaching of the English Language is included as part of the integral formation of the university students. This article deals with the current problem in the English teaching- learning process referred to the insufficient motivation on the university students towards the learning of this language, a matter of vital importance for the development of habits and abilities, which allow them to get a better communicative competence. This work aims to elaborate a system of activities to favor motivation on the students. In order to carry out this investigation, theoretical, empirical and statistical methods were used. This research was useful to the improvement of the English teaching- learning process, particularly to the development of motivation on students of second level of the Information Technology career at the Faculty of Technical Sciences at the Southern State University of Manabí.
Keywords: motivation; intrinsic; extrinsic; motive